Novel sprayable antiskid resin coating

By using new anti-slip coatings based on flaxseed oil and sunflower oil and microencapsulated nanofibers, the problem of insufficient performance of traditional anti-slip coatings in certain application scenarios is solved, and high anti-slip angle, strong adhesion, excellent wear resistance and good weather resistance are achieved, and it meets environmental protection requirements.

CN119552571APending Publication Date: 2025-03-04MIANYANG JINWEI MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411439788.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In some application scenarios, existing anti-slip coatings have insufficient anti-slip angle, insufficient adhesion, and insufficient durability. The traditional method uses a large number of inorganic fillers to cause poor flexibility and wear resistance of the coating, which is harmful to the environment and human health.

Method used

Bio-based polyurethane resin based on flaxseed oil and sunflower oil is used, combined with microencapsulated nanofibers, to form a new sprayable anti-slip resin coating. The coating is prepared by transesterification and cross-linking reaction, ensuring the environmental protection and performance of the material.

Benefits of technology

It significantly improves the anti-slip performance, adhesion and durability of the coating, with an anti-slip angle of more than 70 degrees, an adhesion level of 0, and excellent wear and weather resistance, meeting the requirements of environmental protection and sustainable development.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a novel sprayable antiskid resin coating which comprises the following raw materials in percentage by weight: 30%-60% of bio-based elastic resin, 5%-15% of a curing agent, 5%-15% of a plasticizer, 2%-10% of an accelerant, 1%-5% of a flatting agent, 1%-5% of microencapsulated nanofibers and 1%-5% of a wetting agent. The bio-based elastic resin is a mixture of flaxseed oil-based polyurethane resin and sunflower seed oil-based polyurethane resin, the flaxseed oil-based polyurethane resin accounts for 50%-70% of the total amount of the bio-based elastic resin, and the sunflower seed oil-based polyurethane resin accounts for 30%-50% of the total amount of the bio-based elastic resin. The core of the novel sprayable antiskid resin coating provided by the invention is that the bio-based polyurethane resin based on the linseed oil and the sunflower seed oil is used, and the microencapsulated nanofibers are combined, so that remarkable performance improvement and environmental protection advantages are realized in multiple aspects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coatings, in particular to a novel sprayable anti-slip resin coating. Background Art

[0002] Anti-slip coatings are of great significance in daily life and industrial applications. They are widely used in places such as floors, stairs, ramps, public facilities, and transportation to increase the friction coefficient of the surface and reduce the occurrence of slip accidents. Especially in humid or greasy environments, the performance of anti-slip coatings is more critical. Traditional anti-slip coatings mainly rely on the addition of inorganic fillers (such as quartz sand, aluminum powder, etc.) to increase the surface roughness, but this method often results in poor flexibility and wear resistance of the coating, and easy to fall off. Traditional anti-slip coatings mostly use petroleum-based resins, which release harmful substances during the production and use of these resins, causing negative impacts on the environment and human health. Due to the addition of a large amount of inorganic fillers, traditional anti-slip coatings have poor flexibility and wear resistance, are prone to cracking and peeling, and have a short service life. The construction process of traditional anti-slip coatings is relatively complicated, requiring multiple coatings and a long curing time, which increases construction costs and time. Coatings with a large amount of inorganic fillers often affect the flatness and aesthetics of the surface and are not suitable for application scenarios with high requirements for surface quality.

[0003] With the increasing awareness of environmental protection and the demand for sustainable development, the development of new environmentally friendly anti-skid resin coatings has become an urgent need. Although the existing solvent-free environmentally friendly anti-skid resin coatings have good performance in terms of environmental protection and anti-skid performance, they still have shortcomings in some application scenarios, such as insufficient anti-skid angle, adhesion needs to be improved, and insufficient durability in extreme environments. Therefore, we need to develop a new type of sprayable filler-free anti-skid resin coating to further improve its anti-skid performance, adhesion and durability. Summary of the invention

[0004] The purpose of the present invention is to provide a new type of sprayable anti-slip resin coating to solve the problems raised in the above-mentioned background technology. This technical solution can use superconducting materials (graphene) to make heat-conducting plates, which can be combined with cooling fans, coolants, cooling pipes and other components to achieve better heat dissipation effects.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] The invention discloses a novel sprayable anti-skid resin coating, which is characterized by comprising the following raw materials in percentage by weight:

[0007] Bio-based elastic resin 30% to 60%, curing agent 5% to 15%, plasticizer 5% to 15%, accelerator 2% to 10%, leveling agent 1% to 5%, microencapsulated nanofiber 1% to 5%, wetting agent 1% to 5%.

[0008] Furthermore, the bio-based elastic resin is a mixture of linseed oil-based polyurethane resin and sunflower oil-based polyurethane resin, the linseed oil-based polyurethane resin accounts for 50% to 70% of the total amount of the bio-based elastic resin, and the sunflower oil-based polyurethane resin accounts for 30% to 50% of the total amount of the bio-based elastic resin.

[0009] Furthermore, the preparation method of the bio-based elastic resin includes the steps of: mixing linseed oil and sunflower oil in proportion, pre-treating, removing impurities and moisture, converting the vegetable oil into reactive polyester polyols through ester exchange reaction, reacting the pre-treated polyester polyols with polyisocyanates under the action of a catalyst under nitrogen protection, controlling the reaction temperature between 70°C and 90°C, and reacting for 2 to 4 hours to ensure that the reaction is complete to generate a bio-based polyurethane resin, and after the reaction is completed, cooling the product to room temperature, filtering to remove unreacted raw materials and by-products, and vacuum degassing the bio-based polyurethane resin to ensure that no bubbles remain.

[0010] Furthermore, the curing agent is one of hexamethylene diisocyanate and isophorone diisocyanate, the plasticizer is sebacic acid ester, the accelerator is a silane coupling agent, the leveling agent is a natural wax emulsion, and the wetting agent is one of polyoxyethylene ether and polyoxypropylene ether.

[0011] Furthermore, the raw materials of microencapsulated nanofibers include natural cellulose, microcapsule wall materials, crosslinking agents, and catalysts. The natural cellulose includes one or more of cotton, wood pulp, bamboo, and hemp. The microcapsule wall materials include one of polyurethane, polyacrylate, gelatin, and chitosan. The crosslinking agent includes one of glutaraldehyde, melamine formaldehyde resin, and epichlorohydrin. The catalyst includes an acidic catalyst.

[0012] Furthermore, the preparation method of microencapsulated nanofibers comprises the steps of:

[0013] The natural cellulose raw material is pretreated to remove impurities and moisture, the pretreated cellulose raw material is mechanically ground or chemically treated to obtain cellulose nanofibers, the cellulose raw material is decomposed into nano-scale fibers by acid treatment, and excess acid is removed through centrifugation and washing steps to obtain pure cellulose nanofibers, a polymer selected as a microcapsule wall material is dissolved in a solvent to prepare a polymer solution, a cross-linking agent is added to the polymer solution, and stirred evenly to form a cross-linking system, the cellulose nanofibers are dispersed in water to form a stable suspension, and a mixture of the polymer solution and the cross-linking agent is added to the cellulose nanofiber suspension and stirred at high speed , forming a uniform emulsion; continuing to stir the emulsion at a temperature of 40°C to 60°C to allow the cross-linking reaction to proceed. During the reaction, the polymer forms a stable wall material on the surface of the cellulose nanofibers to form a microcapsule structure; after the reaction is completed, the emulsion is cooled to room temperature to stop the cross-linking reaction; the microencapsulated nanofibers are separated from the emulsion by centrifugation or filtration; the microcapsules are washed with deionized water to remove unreacted raw materials and by-products; the separated microencapsulated nanofibers are dried by vacuum drying or spray drying, and the dried microencapsulated nanofibers are stored in a dry, light-proof environment to ensure their stability and activity.

[0014] A novel method for preparing a sprayable anti-skid resin coating comprises the following steps: firstly, evenly mixing a bio-based elastic resin, a plasticizer, an accelerator and a wetting agent to form a basic mixture; slowly adding a curing agent to the basic mixture and continuously stirring until the mixture is completely mixed; adding microencapsulated nanofibers to the mixed coating and continuously stirring until the mixture is uniform; and filtering the mixture using a fine mesh filter to remove existing impurities or particles that are not fully dispersed.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The present invention provides a new type of sprayable anti-slip resin coating, the core of which is to use bio-based polyurethane resin based on linseed oil and sunflower oil, combined with microencapsulated nanofibers, thereby achieving significant performance improvements and environmental advantages in many aspects. The following is an analysis of the core beneficial effects of this application:

[0017] 1. Environmental protection and sustainability

[0018] Bio-based raw materials: Flaxseed oil and sunflower oil are both renewable resources. Their production and use have little impact on the environment and meet the requirements of sustainable development.

[0019] No toxic chemicals: No toxic or harmful chemicals are used in the synthesis process of bio-based polyurethane resin, ensuring the safety and environmental protection of the coating.

[0020] Solvent-free properties: The paint is solvent-free, avoiding the emission of volatile organic compounds (VOCs) and reducing pollution to the atmosphere.

[0021] 2. Excellent mechanical properties

[0022] Flexibility: Highly unsaturated linseed oil forms a complex three-dimensional network structure in polyurethane resin, which improves the flexibility of the resin. This structure can effectively disperse stress and reduce the occurrence of cracks when subjected to force.

[0023] Wear resistance: Sunflower oil-based polyurethane resin has high chemical stability and antioxidant properties, can provide better durability and anti-aging properties, and ensure that the coating maintains good performance in long-term use.

[0024] 3.Excellent anti-slip performance

[0025] Microencapsulated nanofibers: Microencapsulated nanofibers deform when under pressure, increasing the microscopic roughness of the surface, thereby increasing friction and significantly improving the anti-slip angle of the coating. Experimental verification shows that the anti-slip angle reaches more than 70 degrees, far higher than the industry standard of 60 degrees.

[0026] Uniform dispersion: Microencapsulation technology ensures uniform distribution of cellulose nanofibers in the coating, avoiding local aggregation and improving overall performance.

[0027] 4. Excellent adhesion and leveling properties

[0028] Adhesion: By using silane coupling agent as a promoter, the adhesion between the coating and the substrate is improved, ensuring the firmness and durability of the coating.

[0029] Leveling: Natural wax emulsion acts as a leveling agent, which improves the leveling of the coating and makes the coating surface smoother and more uniform.

[0030] 5. Weather resistance

[0031] Aging resistance: Sunflower oil-based polyurethane resin has good antioxidant properties and can effectively resist the influence of ultraviolet rays and humid and hot environments, ensuring that the coating maintains good performance in long-term use.

[0032] Artificial weathering test: After 1000 hours of light and humidity cycles, the coating showed no obvious fading, cracking or peeling, indicating good weather resistance.

[0033] 6. Easy construction

[0034] Spraying construction: The paint adopts spraying construction method, which is easy to operate, suitable for large-area construction, and improves construction efficiency.

[0035] Curing conditions: After standing at room temperature for 10 minutes, place the sprayed substrate in an oven at 60℃~80℃ for heating and curing for 15~30 minutes. The curing conditions are mild and convenient for practical application.

[0036] Summarize

[0037] Through the above analysis, it can be seen that the new sprayable anti-slip resin coating provided by the present invention has significant advantages in many aspects:

[0038] Environmentally friendly and sustainable: Uses renewable resources, no toxic chemicals, no solvents.

[0039] Excellent mechanical properties: flexibility and wear resistance are significantly improved.

[0040] Excellent anti-slip performance: the anti-slip angle reaches more than 70 degrees.

[0041] Excellent adhesion and leveling properties: ensure the firmness and surface quality of the coating.

[0042] Good weather resistance: maintains good performance during long-term use.

[0043] Easy construction: spraying construction is convenient and the curing conditions are mild.

[0044] These beneficial effects make the coating perform well in anti-slip angle, adhesion, wear resistance and weather resistance, and it has high practical value and market prospects. DETAILED DESCRIPTION

[0045] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] The novel sprayable anti-skid resin coating provided by the present invention comprises the following raw materials in percentage by weight:

[0047] Bio-based elastic resin 30% to 60%, curing agent 5% to 15%, plasticizer 5% to 15%, accelerator 2% to 10%, leveling agent 1% to 5%, microencapsulated nanofiber 1% to 5%, wetting agent 1% to 5%.

[0048] Among them, bio-based elastic resin is one of the key components of the new environmentally friendly anti-slip resin coating, and its selection and performance have an important impact on the overall performance of the coating. Although traditional polyurethane resins have good mechanical properties, their raw materials mostly come from petroleum, which does not meet the requirements of environmental protection and sustainable development. Therefore, choosing bio-based polyurethane resins based on plant oils (such as linseed oil and sunflower oil) can not only improve the environmental protection of the coating, but also bring significant improvements in flexibility and wear resistance.

[0049] The bio-based elastic resin is a mixture of linseed oil-based polyurethane resin and sunflower oil-based polyurethane resin, wherein the linseed oil-based polyurethane resin accounts for 50% to 70% of the total bio-based elastic resin and the sunflower oil-based polyurethane resin accounts for 30% to 50% of the total bio-based elastic resin.

[0050] Linseed oil contains a large amount of linoleic acid and linolenic acid. These unsaturated fatty acids can form a complex three-dimensional network structure through chemical reactions, improving the flexibility and wear resistance of the resin. Linseed oil is a renewable resource, and its production and use have little impact on the environment.

[0051] Sunflower oil contains more monounsaturated fatty acids, such as oleic acid, which have good chemical stability and antioxidant properties, and can improve the durability and anti-aging properties of resins. Sunflower oil has high yield and relatively low price, making it suitable for large-scale production.

[0052] The preparation method of the bio-based elastic resin comprises the steps of:

[0053] Pretreatment: Linseed oil and sunflower oil are mixed in proportion and pretreated to remove impurities and moisture. Vegetable oil is converted into reactive polyester polyols through transesterification.

[0054] To synthesize bio-based polyurethane resin, under nitrogen protection, the pretreated polyester polyol is reacted with polyisocyanate (such as MDI or TDI) under the action of a catalyst (such as dibutyltin dilaurate) to generate bio-based polyurethane resin. The reaction temperature is controlled between 70°C and 90°C, and the reaction time is 2 to 4 hours to ensure that the reaction is complete.

[0055] After the reaction is completed, the product is cooled to room temperature and filtered to remove unreacted raw materials and by-products. The bio-based polyurethane resin is vacuum degassed to ensure that no bubbles remain.

[0056] Highly unsaturated linseed oil forms a complex three-dimensional network structure in the polyurethane resin, which improves the flexibility and wear resistance of the resin. This structure can effectively disperse stress and reduce the occurrence of cracks when subjected to force. Highly stable sunflower oil-based polyurethane resin can provide better durability and anti-aging properties, ensuring that the coating maintains good performance during long-term use. Both linseed oil and sunflower oil are renewable resources, and their production and use have little impact on the environment, meeting the requirements of sustainable development. Bio-based polyurethane resin does not use toxic and harmful chemicals during the synthesis process, ensuring the safety and environmental protection of the coating. Synergistically with bio-based anti-slip additives (such as microencapsulated nanofibers), the anti-slip angle is further improved to more than 60 degrees, or even more than 70 degrees.

[0057] By selecting bio-based polyurethane resins based on linseed oil and sunflower oil, the new sprayable filler-free anti-slip resin coating has been significantly improved in flexibility and wear resistance, while maintaining environmental protection and solvent-free characteristics. This coating performs well in anti-slip angle, adhesion and durability, and has high practical value and market prospects.

[0058] The curing agent is one of hexamethylene diisocyanate and isophorone diisocyanate, the plasticizer is sebacic acid ester, the accelerator is a silane coupling agent, the leveling agent is a natural wax emulsion, and the wetting agent is one of polyoxyethylene ether and polyoxypropylene ether.

[0059] Microencapsulated nanofibers are a special material that can deform when compressed, thereby increasing friction and improving anti-slip properties. The following is a detailed introduction to the raw material selection and preparation method of microencapsulated nanofibers.

[0060] Raw material selection:

[0061] Natural cellulose: Natural cellulose can be extracted from a variety of plants, common sources include cotton, wood pulp, bamboo, hemp, etc. Natural cellulose has good biodegradability and environmental friendliness, and is a renewable resource.

[0062] Microcapsule wall materials: Microcapsule wall materials include polyurethane, polyacrylate, gelatin, chitosan, etc. These polymers have good film-forming properties and mechanical strength, and can effectively coat cellulose nanofibers to prevent them from aggregating in the coating.

[0063] Cross-linking agent: Cross-linking agents include glutaraldehyde, melamine formaldehyde resin, epichlorohydrin, etc. Cross-linking agents can enhance the stability and mechanical strength of microcapsule wall materials and improve the durability of microcapsules.

[0064] Catalyst: Catalysts include acidic catalysts (such as sulfuric acid, p-toluenesulfonic acid) and alkaline catalysts (such as sodium hydroxide). Catalysts can accelerate the cross-linking reaction and improve the preparation efficiency of microcapsules.

[0065] The method for preparing microencapsulated nanofibers comprises the following steps:

[0066] Pre-treating natural cellulose raw materials (such as cotton and wood pulp) to remove impurities and moisture, and mechanically grinding or chemically treating the pre-treated cellulose raw materials to obtain cellulose nanofibers;

[0067] Using acid treatment (such as sulfuric acid) or enzyme treatment (such as cellulase) to decompose the cellulose raw material into nano-scale fibers, and removing excess acid or enzyme through centrifugation and washing steps to obtain pure cellulose nanofibers;

[0068] Dissolving a selected polymer (e.g., polyurethane, polyacrylate) in an appropriate solvent to prepare a polymer solution; adjusting the concentration of the polymer solution to ensure that it is suitable for the subsequent microencapsulation process;

[0069] Add a crosslinking agent (such as glutaraldehyde) to the polymer solution, stir evenly to form a crosslinking system, and adjust the amount of the crosslinking agent to ensure that the microcapsule wall material has sufficient mechanical strength and stability;

[0070] The cellulose nanofibers are dispersed in water to form a stable suspension, a mixture of a polymer solution and a crosslinking agent is added to the cellulose nanofiber suspension, and stirred at high speed to form a uniform emulsion. The emulsion is continuously stirred at a certain temperature of 40°C to 60°C to allow the crosslinking reaction to proceed. During the reaction, the polymer forms a stable wall material on the surface of the cellulose nanofibers to form a microcapsule structure.

[0071] After the reaction is completed, the emulsion is cooled to room temperature to stop the cross-linking reaction, the microencapsulated nanofibers are separated from the emulsion by centrifugation or filtration, and the microcapsules are washed with deionized water to remove unreacted raw materials and by-products;

[0072] The separated microencapsulated nanofibers are dried by vacuum drying or spray drying. The dried microencapsulated nanofibers are stored in a dry, light-proof environment to ensure their stability and activity.

[0073] The microencapsulated nanofibers prepared by the above method have good mechanical properties and anti-slip properties. These fibers deform when compressed, increasing the microscopic roughness of the surface, thereby increasing friction and significantly improving the anti-slip angle of the coating. In addition, the microencapsulation technology can ensure that the cellulose nanofibers are evenly distributed in the coating, avoiding local aggregation and improving the overall performance. This improvement not only meets the requirements of environmental protection and sustainable development, but also ensures that the coating performs well in various application scenarios.

[0074] The present application also provides a method for preparing a novel sprayable anti-slip resin coating, comprising the steps of: first, evenly mixing a bio-based elastic resin, a plasticizer, an accelerator and a wetting agent to form a basic mixture; slowly adding a curing agent to the basic mixture, and continuously stirring until completely mixed; adding microencapsulated nanofibers to the mixed coating, and continuing to stir until uniform; filtering the mixture with a fine mesh filter to remove existing impurities or inadequately dispersed particles; and placing the filtered coating into an appropriate container and sealing it for storage.

[0075] Construction method

[0076] Surface pretreatment: Use an environmentally friendly cleaner to thoroughly clean the surface of the substrate to ensure that there is no pollution such as grease, dust, etc.

[0077] Construction: Spray the paint evenly on the surface of the substrate, and apply multiple layers as needed.

[0078] Curing: After standing at room temperature for a period of time, place the sprayed substrate in an oven at 60℃~80℃ for heating and curing for 15~30 minutes. The specific time depends on the coating thickness and environmental conditions.

[0079] Example 1: Preparation of a novel sprayable anti-slip resin coating

[0080] Ingredients include:

[0081] 60g of bio-based elastic resin: 42g of linseed oil-based polyurethane resin, 18g of sunflower oil-based polyurethane resin; curing agent: 10g of hexamethylene diisocyanate (HDI);

[0082] Plasticizer: sebacate 10 g;

[0083] Accelerator: silane coupling agent 6 grams;

[0084] Leveling agent: 3g natural wax emulsion;

[0085] 3 g of microencapsulated nanofibers;

[0086] Wetting agent: polyoxyethylene ether 3 g;

[0087] Catalyst: dibutyltin dilaurate: 1 g;

[0088] Preparation of bio-based elastic resin:

[0089] Pretreatment: Linseed oil and sunflower oil are mixed in proportion (70% linseed oil, 30% sunflower oil), pretreated to remove impurities and moisture, and the vegetable oil is converted into reactive polyester polyols through transesterification.

[0090] Synthesis of bio-based polyurethane resin: Under nitrogen protection, the pretreated polyester polyol is reacted with polyisocyanate (HDI) in the presence of a catalyst (dibutyltin dilaurate), the reaction temperature is controlled at 80°C, the reaction time is 3 hours, and the reaction is ensured to be complete.

[0091] Post-treatment: After the reaction is completed, the product is cooled to room temperature, filtered to remove unreacted raw materials and by-products, and the bio-based polyurethane resin is vacuum degassed to ensure that no bubbles remain.

[0092] Preparation of microencapsulated nanofibers:

[0093] Raw material processing: The natural cellulose raw material (such as wood pulp) is pretreated to remove impurities and moisture, and the pretreated cellulose raw material is mechanically ground to obtain a cellulose nanofiber suspension. Excess moisture is removed through centrifugation and washing steps to obtain pure cellulose nanofibers.

[0094] Preparation of microcapsule wall material: dissolve polyurethane in a proper amount of solvent to prepare a polyurethane solution, add glutaraldehyde into the polyurethane solution, stir evenly, and form a cross-linking system.

[0095] Microencapsulation process: cellulose nanofibers are dispersed in water to form a stable suspension, a mixture of polyurethane solution and glutaraldehyde is added to the cellulose nanofiber suspension, and stirred at high speed to form a uniform emulsion. The emulsion is continued to be stirred at 50°C to allow the cross-linking reaction to proceed for 2 hours. After the reaction is completed, the emulsion is cooled to room temperature, and the microencapsulated nanofibers are separated by centrifugation. The microcapsules are washed with deionized water to remove unreacted raw materials and by-products, and the separated microencapsulated nanofibers are vacuum dried to obtain dry microencapsulated nanofibers.

[0096] Preparation of coating:

[0097] The bio-based elastic resin (60 g), plasticizer (10 g), accelerator (6 g) and wetting agent (3 g) were mixed evenly to form a base mixture. The curing agent (HDI, 10 g) was slowly added to the base mixture and stirred for 10 minutes until it was completely mixed. The microencapsulated nanofibers (3 g) were added to the mixed coating and stirred for 15 minutes to ensure uniform dispersion. The mixture was filtered through a fine mesh filter to remove impurities or inadequately dispersed particles. The filtered coating was placed in an appropriate container and sealed for storage.

[0098] Construction method:

[0099] Surface pretreatment: Use an environmentally friendly cleaner to thoroughly clean the surface of the substrate to ensure that there is no pollution such as grease, dust, etc.

[0100] Construction: Spray the paint evenly on the surface of the substrate, and apply multiple layers as needed.

[0101] Curing: After standing at room temperature for 10 minutes, the sprayed substrate was placed in an oven at 70°C for heating and curing for 20 minutes.

[0102] Performance Test:

[0103] Anti-slip performance:

[0104] Test method: Anti-slip angle test is carried out according to ASTM D2047 standard.

[0105] Test results: The anti-slip angle reaches 72 degrees, which is much higher than the industry standard of 60 degrees.

[0106] Adhesion:

[0107] Test method: Cross-cut test according to ISO 2409 standard.

[0108] Test results: The adhesion grade is 0, indicating that the adhesion between the coating and the substrate is very strong.

[0109] Abrasion resistance:

[0110] Test method: Taber abrasion test was performed according to ASTM D4060.

[0111] Test results: The wear index is 0.02mg / 1000cycles, indicating that the coating has excellent wear resistance.

[0112] Weather resistance:

[0113] Test method: Artificial weathering test is carried out in accordance with ISO 11341 standard.

[0114] Test results: After 1000 hours of light and humidity cycles, the coating showed no obvious fading, cracking or peeling, indicating good weather resistance.

[0115] A novel sprayable anti-skid resin coating is prepared by the above-mentioned embodiment. The coating adopts bio-based polyurethane resin based on linseed oil and sunflower oil, which not only improves the flexibility and wear resistance of the coating, but also ensures its environmental protection and sustainable development. The addition of microencapsulated nanofibers significantly improves the anti-skid performance of the coating, making its anti-skid angle reach 72 degrees. The performance test results show that the coating performs well in anti-skid angle, adhesion, wear resistance and weather resistance, and has high practical value and market prospects.

[0116] Example 2: Preparation of a novel sprayable anti-slip resin coating

[0117] The raw materials include: 35 grams of linseed oil-based polyurethane resin, 25 grams of sunflower oil-based polyurethane resin, 12 grams of isophorone diisocyanate (IPDI), 12 grams of sebacate, 4 grams of silane coupling agent, 4 grams of natural wax emulsion, 4 grams of microencapsulated nanofibers, 3 grams of polyoxypropylene ether, and 1 gram of dibutyltin dilaurate.

[0118] The preparation process includes the steps:

[0119] Linseed oil and sunflower oil are mixed in proportion (58.3% linseed oil, 41.7% sunflower oil), pretreated to remove impurities and moisture, and the vegetable oil is converted into reactive polyester polyols through transesterification.

[0120] Under nitrogen protection, the pretreated polyester polyol was reacted with polyisocyanate (IPDI) in the presence of a catalyst (dibutyltin dilaurate), the reaction temperature was controlled at 85° C., and the reaction time was 3 hours to ensure that the reaction was complete.

[0121] After the reaction is completed, the product is cooled to room temperature, filtered to remove unreacted raw materials and by-products, and the bio-based polyurethane resin is vacuum degassed to ensure that no bubbles remain.

[0122] The natural cellulose raw material (such as wood pulp) is pretreated to remove impurities and moisture, and the pretreated cellulose raw material is mechanically ground to obtain a cellulose nanofiber suspension. The excess moisture is removed through centrifugation and washing steps to obtain pure cellulose nanofibers.

[0123] The polyurethane is dissolved in a proper amount of solvent to prepare a polyurethane solution, glutaraldehyde is added into the polyurethane solution, and the mixture is stirred evenly to form a cross-linking system.

[0124] The cellulose nanofibers are dispersed in water to form a stable suspension, a mixture of a polyurethane solution and glutaraldehyde is added to the cellulose nanofiber suspension, and stirred at a high speed to form a uniform emulsion. The emulsion is continued to be stirred at 50°C to allow the cross-linking reaction to proceed for 2 hours. After the reaction is completed, the emulsion is cooled to room temperature, and the microencapsulated nanofibers are separated by centrifugation. The microcapsules are washed with deionized water to remove unreacted raw materials and by-products, and the separated microencapsulated nanofibers are vacuum dried to obtain dry microencapsulated nanofibers.

[0125] The bio-based elastic resin (60 g), plasticizer (12 g), accelerator (4 g) and wetting agent (3 g) were mixed evenly to form a base mixture. The curing agent (IPDI, 12 g) was slowly added to the base mixture and stirred for 10 minutes until it was completely mixed. The microencapsulated nanofibers (4 g) were added to the mixed coating and stirred for 15 minutes to ensure uniform dispersion. The mixture was filtered through a fine mesh filter to remove impurities or inadequately dispersed particles. The filtered coating was placed in an appropriate container and sealed for storage.

[0126] Construction method: Use an environmentally friendly cleaner to thoroughly clean the surface of the substrate to ensure that there is no pollution such as grease, dust, etc. Spray the paint evenly on the surface of the substrate. Multi-layer spraying can be performed as needed. After standing at room temperature for 10 minutes, place the sprayed substrate in a 75°C oven for heating and curing for 20 minutes.

[0127] Performance Testing

[0128] Anti-slip performance:

[0129] Test method: Anti-slip angle test is carried out according to ASTM D2047 standard.

[0130] Test results: The anti-slip angle reaches 70 degrees, which is much higher than the industry standard of 60 degrees.

[0131] Adhesion:

[0132] Test method: Cross-cut test according to ISO 2409 standard.

[0133] Test results: The adhesion grade is 0, indicating that the adhesion between the coating and the substrate is very strong.

[0134] Abrasion resistance:

[0135] Test method: Taber abrasion test was performed according to ASTM D4060.

[0136] Test results: The wear index is 0.03 mg / 1000 cycles, indicating that the coating has excellent wear resistance.

[0137] Weather resistance:

[0138] Test method: Artificial weathering test is carried out in accordance with ISO 11341 standard.

[0139] Test results: After 1000 hours of light and humidity cycles, the coating showed no obvious fading, cracking or peeling, indicating good weather resistance.

[0140] Through the above-mentioned Example 2, a new type of sprayable anti-skid resin coating is prepared. The coating adopts a bio-based polyurethane resin based on linseed oil and sunflower oil, which not only improves the flexibility and wear resistance of the coating, but also ensures its environmental protection and sustainable development. The addition of microencapsulated nanofibers significantly improves the anti-skid performance of the coating, making its anti-skid angle reach 70 degrees. The performance test results show that the coating performs well in anti-skid angle, adhesion, wear resistance and weather resistance, and has high practical value and market prospects.

[0141] Example 3: Preparation of a novel sprayable anti-slip resin coating

[0142] 1. Raw material preparation

[0143] The raw materials include: 36 grams of linseed oil-based polyurethane resin, 24 grams of sunflower oil-based polyurethane resin, 10 grams of isohexamethylene diisocyanate (HDI), 12 grams of sebacic acid ester, 5 grams of silane coupling agent, 3 grams of natural wax emulsion, 3 grams of microencapsulated nanofibers, 3 grams of polyoxyethylene ether, and 1 gram of dibutyltin dilaurate.

[0144] The preparation of the novel sprayable anti-skid resin coating comprises the following steps:

[0145] Linseed oil and sunflower oil are mixed in proportion (60% linseed oil, 40% sunflower oil), pretreated to remove impurities and moisture, and the vegetable oil is converted into reactive polyester polyols through transesterification.

[0146] Under nitrogen protection, the pretreated polyester polyol was reacted with polyisocyanate (HDI) in the presence of a catalyst (dibutyltin dilaurate), the reaction temperature was controlled at 80° C., and the reaction time was 3 hours to ensure that the reaction was complete.

[0147] After the reaction is completed, the product is cooled to room temperature, filtered to remove unreacted raw materials and by-products, and the bio-based polyurethane resin is vacuum degassed to ensure that no bubbles remain.

[0148] The natural cellulose raw material (such as wood pulp) is pretreated to remove impurities and moisture, and the pretreated cellulose raw material is mechanically ground to obtain a cellulose nanofiber suspension. The excess moisture is removed through centrifugation and washing steps to obtain pure cellulose nanofibers.

[0149] The polyurethane is dissolved in a proper amount of solvent to prepare a polyurethane solution, glutaraldehyde is added into the polyurethane solution, and the mixture is stirred evenly to form a cross-linking system.

[0150] The cellulose nanofibers are dispersed in water to form a stable suspension, and a mixture of a polyurethane solution and glutaraldehyde is added to the cellulose nanofiber suspension and stirred at a high speed to form a uniform emulsion. The emulsion is continued to be stirred at 50°C to allow the cross-linking reaction to proceed for 2 hours. After the reaction is completed, the emulsion is cooled to room temperature, and the microencapsulated nanofibers are separated by centrifugation. The microcapsules are washed with deionized water to remove unreacted raw materials and by-products.

[0151] The separated microencapsulated nanofibers are vacuum dried to obtain dry microencapsulated nanofibers.

[0152] The bio-based elastic resin (60 g), plasticizer (12 g), accelerator (5 g) and wetting agent (3 g) were mixed evenly to form a base mixture. The curing agent (HDI, 10 g) was slowly added to the base mixture and stirred for 10 minutes until it was completely mixed. The microencapsulated nanofibers (3 g) were added to the mixed coating and stirred for 15 minutes to ensure uniform dispersion. The mixture was filtered through a fine mesh filter to remove impurities or inadequately dispersed particles. The filtered coating was placed in an appropriate container and sealed for storage.

[0153] Construction method

[0154] Use an environmentally friendly cleaner to thoroughly clean the surface of the substrate to ensure that there is no pollution such as grease, dust, etc., spray the paint evenly on the surface of the substrate, and perform multiple layers of spraying as needed. After standing at room temperature for 10 minutes, place the sprayed substrate in a 70°C oven for heating and curing for 20 minutes.

[0155] Performance Testing

[0156] Anti-slip performance:

[0157] Test method: Anti-slip angle test is carried out according to ASTM D2047 standard.

[0158] Test results: The anti-slip angle reaches 71 degrees, which is much higher than the industry standard of 60 degrees.

[0159] Adhesion:

[0160] Test method: Cross-cut test according to ISO 2409 standard.

[0161] Test results: The adhesion grade is 0, indicating that the adhesion between the coating and the substrate is very strong.

[0162] Abrasion resistance:

[0163] Test method: Taber abrasion test was performed according to ASTM D4060.

[0164] Test results: The wear index is 0.025 mg / 1000 cycles, indicating that the coating has excellent wear resistance.

[0165] Weather resistance:

[0166] Test method: Artificial weathering test is carried out in accordance with ISO 11341 standard.

[0167] Test results: After 1000 hours of light and humidity cycles, the coating showed no obvious fading, cracking or peeling, indicating good weather resistance.

[0168] Through the above-mentioned Example 3, a new type of sprayable anti-skid resin coating is prepared. The coating adopts a bio-based polyurethane resin based on linseed oil and sunflower oil, which not only improves the flexibility and wear resistance of the coating, but also ensures its environmental protection and sustainable development. The addition of microencapsulated nanofibers significantly improves the anti-skid performance of the coating, and its anti-skid angle reaches 71 degrees. The performance test results show that the coating performs well in anti-skid angle, adhesion, wear resistance and weather resistance, and has high practical value and market prospects.

[0169] The present invention provides a novel sprayable anti-slip resin coating, the core of which is the use of bio-based polyurethane resin based on linseed oil and sunflower oil, combined with microencapsulated nanofibers, thereby achieving significant performance improvements and environmental advantages in multiple aspects.

[0170] Improved performance of bio-based elastic resins

[0171] Linseed oil-based polyurethane resin: Linseed oil contains a large amount of linoleic acid and linolenic acid. These unsaturated fatty acids can form a complex three-dimensional network structure through chemical reactions, improving the flexibility and wear resistance of the resin. This structure can effectively disperse stress and reduce the occurrence of cracks when subjected to force.

[0172] Sunflower oil-based polyurethane resin: Sunflower oil contains more monounsaturated fatty acids, such as oleic acid, which have good chemical stability and antioxidant properties, and can improve the durability and anti-aging properties of the resin. Sunflower oil has high yield and relatively low price, making it suitable for large-scale production.

[0173] Anti-slip properties of microencapsulated nanofibers

[0174] Deformation mechanism: Microencapsulated natural cellulose nanofibers deform when compressed, increasing the microscopic roughness of the surface, thereby increasing friction and significantly improving the anti-slip properties of the coating.

[0175] Uniform distribution: Microencapsulation technology can ensure that cellulose nanofibers are evenly distributed in the coating, avoiding local aggregation and improving overall performance.

[0176] The role of other additives

[0177] Curing agent: Hexamethylene diisocyanate (HDI) or isophorone diisocyanate (IPDI) is used as a curing agent to undergo a cross-linking reaction with the hydroxyl and amine groups in the bio-based polyurethane resin to form a network structure with a high cross-linking density, thereby improving the mechanical properties of the coating.

[0178] Plasticizer: Sebacate esters as plasticizers can improve the flexibility and ductility of the coating and reduce the brittleness of the coating.

[0179] Accelerator: Silane coupling agent as an accelerator can improve the adhesion between the coating and the substrate and enhance the durability of the coating.

[0180] Leveling agent: Natural wax emulsion is used as a leveling agent to improve the leveling and surface smoothness of the coating and reduce the orange peel phenomenon of the coating.

[0181] Wetting agent: Polyoxyethylene ether or polyoxypropylene ether as a wetting agent can reduce the interfacial tension between the liquid and the solid surface, allowing the coating to better wet the substrate and improve the adhesion and uniformity of the coating.

[0182] Comprehensive performance improvement

[0183] Anti-slip performance:

[0184] Microencapsulated nanofibers deform when under pressure, increasing the microscopic roughness of the surface, increasing friction, and significantly improving the anti-slip performance of the coating. Test results show that the anti-slip angle reaches more than 70 degrees, far higher than the industry standard of 60 degrees.

[0185] Adhesion:

[0186] The synergistic effect of silane coupling agent and wetting agent improves the adhesion between the coating and the substrate. The test results show that the adhesion level is 0, indicating that the adhesion between the coating and the substrate is very strong.

[0187] Abrasion resistance:

[0188] The complex three-dimensional network structure of the bio-based polyurethane resin and the synergistic effect of the plasticizer improve the flexibility and wear resistance of the coating. The test results show that the wear index is 0.02-0.03 mg / 1000 cycles, indicating that the coating has excellent wear resistance.

[0189] Weather resistance:

[0190] The high stability and antioxidant properties of the sunflower oil-based polyurethane resin, as well as the uniform distribution of microencapsulated nanofibers, improve the weather resistance of the coating. Test results show that after 1,000 hours of light and heat cycles, the coating has no obvious fading, cracking or peeling, indicating good weather resistance.

[0191] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A new type of sprayable anti-slip resin coating, characterized by: The following raw materials are included in weight percentage: Bio-based elastic resin 30% to 60%, curing agent 5% to 15%, plasticizer 5% to 15%, accelerator 2% to 10%, leveling agent 1% to 5%, microencapsulated nanofiber 1% to 5%, wetting agent 1% to 5%.

2. The novel sprayable anti-slip resin coating according to claim 1 is characterized in that: The bio-based elastic resin is a mixture of linseed oil-based polyurethane resin and sunflower oil-based polyurethane resin, wherein the linseed oil-based polyurethane resin accounts for 50% to 70% of the total bio-based elastic resin and the sunflower oil-based polyurethane resin accounts for 30% to 50% of the total bio-based elastic resin.

3. The novel sprayable anti-slip resin coating according to claim 2 is characterized in that: The preparation method of the bio-based elastic resin includes the following steps: mixing linseed oil and sunflower oil in proportion, pre-treating to remove impurities and moisture, converting the vegetable oil into reactive polyester polyols through ester exchange reaction, reacting the pre-treated polyester polyols with polyisocyanates under the action of a catalyst under nitrogen protection, controlling the reaction temperature between 70°C and 90°C, and reacting for 2 to 4 hours to ensure that the reaction is completely carried out to generate a bio-based polyurethane resin, and after the reaction is completed, cooling the product to room temperature, filtering to remove unreacted raw materials and by-products, and vacuum degassing the bio-based polyurethane resin to ensure that no bubbles remain.

4. The novel sprayable anti-slip resin coating according to claim 1 is characterized in that: The curing agent is one of hexamethylene diisocyanate and isophorone diisocyanate, the plasticizer is sebacic acid ester, the accelerator is a silane coupling agent, the leveling agent is a natural wax emulsion, and the wetting agent is one of polyoxyethylene ether and polyoxypropylene ether.

5. The novel sprayable anti-slip resin coating according to claim 1 is characterized in that: The raw materials of microencapsulated nanofibers include natural cellulose, microcapsule wall materials, crosslinking agents, and catalysts. The natural cellulose includes one or more of cotton, wood pulp, bamboo, and hemp. The microcapsule wall materials include one of polyurethane, polyacrylate, gelatin, and chitosan. The crosslinking agent includes one of glutaraldehyde, melamine formaldehyde resin, and epichlorohydrin. The catalyst includes an acidic catalyst.

6. The novel sprayable anti-slip resin coating according to claim 5 is characterized in that: The method for preparing microencapsulated nanofibers comprises the steps of: The natural cellulose raw material is pretreated to remove impurities and moisture, the pretreated cellulose raw material is mechanically ground or chemically treated to obtain cellulose nanofibers, the cellulose raw material is decomposed into nano-scale fibers by acid treatment, and excess acid is removed through centrifugation and washing steps to obtain pure cellulose nanofibers, a polymer selected as a microcapsule wall material is dissolved in a solvent to prepare a polymer solution, a cross-linking agent is added to the polymer solution, and stirred evenly to form a cross-linking system, the cellulose nanofibers are dispersed in water to form a stable suspension, and a mixture of the polymer solution and the cross-linking agent is added to the cellulose nanofiber suspension and stirred at high speed , forming a uniform emulsion; continuing to stir the emulsion at a temperature of 40°C to 60°C to allow the cross-linking reaction to proceed. During the reaction, the polymer forms a stable wall material on the surface of the cellulose nanofibers to form a microcapsule structure; after the reaction is completed, the emulsion is cooled to room temperature to stop the cross-linking reaction; the microencapsulated nanofibers are separated from the emulsion by centrifugation or filtration; the microcapsules are washed with deionized water to remove unreacted raw materials and by-products; the separated microencapsulated nanofibers are dried by vacuum drying or spray drying, and the dried microencapsulated nanofibers are stored in a dry, light-proof environment to ensure their stability and activity.

7. The method for preparing a novel sprayable anti-skid resin coating according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: firstly, mixing the bio-based elastic resin, the plasticizer, the accelerator and the wetting agent uniformly to form a basic mixture; slowly adding the curing agent into the basic mixture and continuously stirring until the mixture is completely mixed; adding the microencapsulated nanofibers into the mixed coating and continuously stirring until the mixture is uniform; and filtering the mixture with a fine mesh filter to remove the existing impurities or particles that are not fully dispersed.